Diferencias culturales y su impacto en el mundo laboral : Chile y Nueva Zelanda en los agro-negocios = Cultural differences and their impact in the working world : Chile and New Zealand in agribusiness : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in at Massey University, New Zealand - Tait, Sarah (Massey University, 2019)
National culture refers to the socially transmitted set of behavioural standards shared by individuals of a nation, which manifest through their personal values, attitudes, cognitive processes, reactions and morals. When it comes to working with individuals from other national cultures, New Zealanders have been criticised for their lack of intercultural ability which is believed to cost them in term of relationships and economic opportunities. New Zealand has growing economic ties with Latin America, but New Zealanders know relatively little about this region’s cultures. This study investigates the experiences had by New Zealand individuals operating business in Southern Chile’s dairy region to better understand how differences in national culture affect their interactions with the local people. A literature review was completed, followed by survey questionnaires and interviews with both New Zealanders and Chileans who have experience working together in this region. The research aimed to identify cultural differences each group perceives in the other and how these differences impact on these groups working together. It was identified that many New Zealanders go to Chile with little language or cultural preparation and the general belief that experience in the market will be the best way to navigate the culture. Chileans believe, however, that New Zealanders’ general lack of language and cultural ability harms how Chileans perceive New Zealanders and that it costs them business relationships in Chile. Chileans claim that New Zealanders’ explicit communication style, lower power distance culture (making them seem impatient in Chile) and their relatively individualistic culture are most difficult for Chileans to understand, accept or work with. While Chileans generally respect New Zealanders in the region, many perceive them as rude (even if just initially) as a result of these differences in culture. New Zealanders feel that the aspects of Chilean culture which have been most difficult to understand, accept or work with include Chile’s relatively higher power distance culture (causing higher levels of bureaucracy and a hierarchical social class system) and the implicit communication style of Chileans. This study captures the journey and struggle New Zealanders have had in understanding Chilean culture, and in becoming more aware of their own national culture and how they must adapt to operate more effectively in the Chilean environment.
Keywords: Agricultural industries; Chile; Management; Business communication; Cross-cultural studies; New Zealand; Intercultural communication; National characteristics, New Zealand; National characteristics, Chilean; 470310 Iberian languages; 300208 Farm management, rural management and agribusiness